Comparative empirical analysis on the effect of mortgage loan on capital adequacy ratio / Yusuf Dinç - Dinç, Yusuf (Universiti Teknologi MARA Selangor, 2017)
Capital adequacy ratio is the main indicator for banks to proceed with their operations. Standards for the calculation of the ratio are based on Basel Accord. Key factor for the calculation is credit risk. Credit risk is a function of credit and collateral type. In this case, mortgage has lower risk weight based on its collateral structure on credit risk. This research evaluates the effects of mortgages on capital adequacy ratio to understand the effects of collateral based credits. The findings show positive results between capital adequacy ratio and mortgages of participation banks. However, mortgages have negative impact on capital adequacy ratio of conventional banks. Participation and conventional banks of Turkey are compared on linear regression to analyse the effects of mortgages on capital adequacy ratio. Results are important for further research and professionals.